Thermodynamic study of combining chemical looping combustion and combined reforming of propane - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Joshi, Ajit R. (Fuel, 2010)
Existing energy generation technologies emit CO(2) gas and are posing a serious problem of global warming and climate change. The thermodynamic feasibility of a new process scheme combining chemical looping combustion (CLC) and combined reforming (CR) of propane (LPG) is studied in this paper. The study of CLC of propane with CaSO(4) as oxygen carrier shows thermodynamic feasibility in temperature range (400-782.95 degrees C) at 1 bar pressure. The CO(2) generated in the CLC can be used for combined reforming of propane in an autothermal way within the temperature range (400-1000 degrees C) at 1 bar pressure to generate syngas of ratio 3.0 (above 600 degrees C) which is extremely desirable for petrochemical manufacture. The process scheme generates (a) huge thermal energy in CLC that can be used for various processes, (b) pure N(2) and syngas rich streams can be used for petrochemical manufacture and (c) takes care of the expensive CO(2) separation from flue gas stream and CO(2) sequestration. The thermoneutral temperature (TNP) of 702.12 degrees C yielding maximum syngas of 5.98 mol per mole propane fed, of syngas ratio 1.73 with negligible methane and carbon formation was identified as the best condition for the CR reactor operation. The process can be used for different fuels and oxygen carriers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Chemical looping combustion; CLC; CO(2) utilization; Energy generation